Silsesquioxane Modified with PAMAM Dendrimer and a Bimetallic Complex for Electrochemical Detection of Ascorbic Acid - Silvestrini Fernandes, Daniela [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (Wiley, 2021)
Octakis(3-chloropropyl)octasilsesquioxane (S) was organofunctionalized with the PAMAM Dendrimer G.0 (SPD). After functionalization, silsesquioxane interacts with copper chloride and subsequently with potassium hexacyanoferrate (III) to produce the structure CuHSPD. The silsesquioxane functionalized with the PAMAM dendrimer (SPD) and the obtained novel hybrid composite (CuHSPD) were characterized by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS). The CuHSP voltammogram showed two well-defined redox pairs with Eθ′= 0.27 and 0.74 V, that are assigned to the CuI/CuII and FeII(CN)6/FeIII(CN)6 redox pairs, respectively. The graphite paste electrode containing CuHSPD allowed the electrocatalytic determination of ascorbic acid using various electrochemical techniques such as cyclic voltammetry, differential pulse voltammetry, and chronoamperometry.
Keywords: Ascorbic Acid; Organofunctionalization; PAMAM dendrimer; Silsesquioxane